The Philippines a natural history - Rees, Colin (Ateneo de Manila University Press, 2016)
"The Philippines: a natural history celebrates the extraordinary beauty and diversity of the Philippines' over 7,000 islands. Richly descriptive of the archipelago's topography, climate, and oceanography, along with its tectonic and geological history, chapters explore prehistory and the early years of indigenous life before moving on to spanish times. Profiled are many of its protected areas, landscapes and seascapes designed to staunch the profound imprint of human activity that threaten's the country's biodiversity. The alarming decline of flora and fauna and the threat posed to many species has caused many renowned conservationists to write off the country as a global biodiversity area. Yet hope remains, and a concluding chapter takes stock of what remains, and what actions are being taken to rescue this treasure from possible loss-a siren call to Filipinos and others to preserve one of the wonders of this world. It is hoped that this book will renew the commitment among teachers, students, policymakers, and citizen to protect this "Pearl of the Orient."--Cover.